NILAI-NILAI RUMAH TANGGA DALAM NOVEL-NOVEL AHMAD TOHARI: TRILOGI RONGGENG DUKUH PARUK, BEKISAR MERAH DAN BELANTIK - Mugijatna, Mugijatna (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2011)
This study is cunducted to discuss the problem of household values in Ahmad Tohari’s novels: Ronggeng Dukuh Paruk trilogy, Bekisar Merah and Belantik (Bekisar Merah II). As for the purpose is to describe household values in the novels, to describe Ahmad Tohari’s intention to reveal household values in the novels, and to describe the significance of household values in the novels. This study uses cultural approach with hermeneutics as its methodology and semiotics as its analysis. The findings are, first, household values in Ronggeng Dukuh Paruk trilogy is expressed in a form of Rasus’ refusal toward pornographic ronggeng tradition and Srintil’s struggle to become domestic woman. In Bekisar Merah and Belantik, it is expressed in a form of Kanjat’s attitude to marry Lasi honorably and Lasi’s refusal to have sexual intercourse outside marriage. Second, Ahmad Tohari’s intention to express household values in the novels is to develop civilization which is clean from immorality. Third, the significance of household values in the novels is as ’model of” inherited values, at the same time as ’model for’ struggle to continue the inherited values. Besides that, the values also have a significance of ”a candle in darkness” to face tradition which nurture sexual intercourse outside marriage and the promulgation of sexual intercourse outside marriage by hedonistic life.